Interactive Effects of Soil Lead and Cadmium on Dry Matter Yield and Metal Content of Indian Mustard (Brassica juncea (L.) Czern) - Deepika Sharma; R. Sikka; Dhanwinder Singh (Journal of the Indian Society of Soil Science, 2023)
Lead (Pb) and cadmium (Cd) are known to influence each other’s uptake by plants when they coexist in the soil in significant amounts. This influence can be useful if it is antagonistic but may be detrimental if synergistic. In a screenhouse, interactive effects of soil Cd (0, 10, 25, 50 and 100 mg kg-1) and Pb (0, 25, 50, 100 and 200 mg kg-1) were studied on dry matter yield (DMY), Cd and Pb content in Indian mustard (Brassica juncea (L.) Czern) grown for 60 days in a loamy sand soil. The DMY was recorded and plants were analyzed for total Cd and Pb contents. In equilibrated soil there was significant increase in the mean DTPA-Cd and DTPA-Pb with increase in levels of their respective spiking. The content of DTPA-Cd increased significantly where different combinations of Cd and Pb were applied whereas, DTPA-Pb significantly decreased when Pb was applied in combination with Cd. At Cd+200 mg Pb kg-1 soil and Pb+100 mg Cd kg-1 soil, the mean shoot DMY of Indian mustard decreased by 55.8 and 57.7 per cent, respectively as compared to control. The mean shoot Cd content of Indian mustard increased by 9.9 per cent with application of Cd+200 mg Pb kg-1 soil while the mean Pb content decreased by 10.4 per cent with application of Pb+100 mg Cd kg-1 soil as compared to their respective single treatments. The post-harvest soil DTPA-Cd and Pb decreased as compared to their pre-sowing contents but considerable residual contents still remained in soil. An additive adverse effect of the metals on DMY, Pb and Cd content of the crop was observed.